Body composition and fitness profile of Polish top u15 male handball players: talent identification and selection model for sport high schools - Wartalowicz, M. H.; Plusa, J.; Przystupinska, A. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were to assess the positional differences in body composition and selected motor abilities of male Polish U15 team handball (TH) players who applied to the Polish Handball Federation (PHF) sport high schools (HS) in 2019 and to compare differences in the tested characteristics between selected and rejected candidates. Ninety male players, born in 2004-2005, were tested in body composition, running speed (20 m), countermovement jump (CMJ), and 2 kg medicine ball overhead throw (MBT). The level of significance was set at p < 0.05. Anthropometric data revealed significant differences in body height (p = 0.002, Eta2p = 0.168), body mass (BM) (p < 0.001, Eta2p = 0.367), BM index (BMI) (p < 0.001, Eta2p = 0.270), body fat percentage (FAT) (p = 0.003, Eta2p = 0.152), and fat-free mass (FFM) (p < 0.001, Eta2p = 0.356). Position-specific differences were observed, wherein pivots were the tallest and heaviest, having the highest BMI, FAT, and FFM whereas the wings were the smallest and lightest, with the lowest BMI, FAT, and FFM. Regarding fitness parameters, no significant differences in CMJ or MBT were observed. Backcourt players were faster than pivots on the 20-m sprint (p = 0.029, Eta2p = 0.104). Findings did not confirm expected anthropological and fitness differences between rejected vs. accepted candidates to the PHF sport HS. The only significant positional difference noted was that rejected pivots had 28.3% higher FAT levels than accepted. Our data indicate that the training of young TH players should target key functional, position specific, upper-body, and lower-body strength qualities, which enable them to successfully execute challenging game situations.